Don't Believe the Hype: Local Media Slant, Local Advertising, and Firm Value - GURUN, UMIT G.; BUTLER, ALEXANDER W. (Journal of Finance, 2012)
ABSTRACT When local media report news about local companies, they use fewer negative words compared to the same media reporting about nonlocal companies. We document that one reason for this positive slant is the firms' local media advertising expenditures. Abnormal positive local media slant strongly relates to firm equity values. The effect is stronger for small firms; firms held predominantly by individual investors; and firms with illiquid or highly volatile stock, low analyst following, or high dispersion of analyst forecasts. These findings show that news content varies systematically with the characteristics and conflicts of interest of the source.